Análisis del sistema producción de leche de la finca "La Luna" en el cantón de San Carlo - González-Luna, Luis Alonso (Instituto Tecnológico de Costa Rica, 2015)
The study consisted the development of a general diagnosis of the Dairy farm “La Luna”, located in the village of Altamirita, district of Aguas Zarcas, canton San Carlos, province Alajuela. The research had as purpose to make a proposal that give solution to a deficiency detected on the dairy farm. The study included the analysis of forage resources, animal resources and production, equipment, infrastructure and human resources. The evaluation of the above variable was performed by means of a SWOT analysis, whereby weaknesses are categorized by priority order of resolution, determining the most important aspect on which the study was developed. The priority areas that were identified were, that the farm does not have a defined crossing system, reproductive parameters such as the heat detection percentage, service per conception and age at first calving are below the national parameters and there is no well defined selection pressure on heifer growth. The proposal developed in this work was focused on the aspect of reproductive parameters bringing the animals to a lower age to first calving, increasing the heat detection parameter and reducing service per conception.
Proyecto de graduación (Bachillerato en Ingeniería en Agronomía) Instituto Tecnológico de Costa Rica, Escuela de Ingeniería en Agronomía, 2015
Keywords: Ganado de leche; Perfeccionamiento del hato; Fincas; Mejoramiento